Clinico-demographic characteristic and outcome of adult acute organophosphorus (OP) poisoning in Teaching Hospital of Madhesh Province, Nepal - Subedi, Dharma Datta; Kandel, Shiva (Janaki Medical College Journal of Medical Science, 2024)
Background & Objectives: Organophosphorus (OP) poisoning is a major health problem worldwide, especially in developing countries. This study aimed to find out the demographic, clinical presentation and outcome of OP poisoning patients. Materials and Methods: A cross-sectional study of two years duration was conducted on patients presenting to Emergency Department (ER) with clinical features of OP poisoning at Janaki Medical College Teaching Hospital (JMCTH), a tertiary care hospital. Results: A total of 84 cases of acute poisoning were reported in ER-JMCTH. Patient ages ranged from 15 to 60 years. The highest number of poisoning cases was observed in the 15-25 years age group (44 cases 52.4%) male = 33 (39.3%) and female = 51(60.7%), ratio M: F = (1:1.5). Most cases of poisoning were due to suicidal intention (n = 63, 75%), most common toxic substances used for suicidal purposes of OP were chlorpyriphos (n = 56, 66.7%) and dichlorvos (n = 17, 20.2%). Most of the cases belonged to illiterate (n = 26, 31%) and primary education (n=19, 22.6%). About 79.8% of the patient’s symptoms were cholinergic effect (muscarinic), 9.5% nicotinic and 10.7% central nervous system (CNS) effect. Nearly 93% (n = 78) patients survived and 7% resulted in death. Conclusion: The majority of OP poisoning patients were of young age and OP poisoning was more common in women compared to men. Suicidal poisonings were more frequent than accidental ones. The research team's a treating physicians noted miosis as the most common symptom, whereas patients most frequently complained of nausea and vomiting.